Psychological analysis of “The Woodsman” movie - Arboccó de los Heros, Manuel (2013)
The following article is an attempt to present the psychological analysis of a film by NicoleKassell, director of cinema of the United States, entitled “The Woodsman” or “The lumberjack”,a movie that is the story of Walter, a former inmate who spends twelve years in prison for sexualcrimes committed to girls and after completing his sentence, released from prison to enter ina society which is not located which does not feel belong and which remind continuously thepathological of his being. From what is shown in the film, the particularities in the experience ofthe protagonist, the diagnosis of pedophilia, will review possibilities of his childhood psychosexualdevelopment, its link with a colleague and the role of the society in similar cases.